Effects of the "Care for Participation+" Intervention on the Participation of Adults With Visual and Severe or Profound Intellectual Disabilities: A Nonrandomized Controlled Trial. Issue 2 (22nd October 2021) - Hanzen, Gineke; Waninge, Aly; van Nispen, Ruth M. A.; Vlaskamp, Carla; van der Putten, Annette A. J.
Abstract: Background: The "Care for Participation+" (CFP+) intervention was developed in order to change the attitudes of direct support professionals (DSPs) regarding the participation of adults with visual and severe or profound ID (VSPID). Aims: The aim of this study was to evaluate the effects of CFP+ on the participation of the target group. Methods: We performed a pilot nonrandomized controlled trial with three arms. The effect of CFP+ on participation was compared to a usual care control group ( n  = 13), and a control group in which one element of CFP+ was implemented ( n  = 14). Participation was measured using specific domains of the Quality Of Life of People with Profound Multiple Disabilities (QOL‐PMD) questionnaire that was completed by the legal representatives and DSPs of adults with VSPID, and video‐observations of (initiatives for prompting) active involvement within 10 dyads comprising adults with VSPID and DSPs. Findings: The effects of CFP+ on the QOL‐PMD were very small and not statistically significant. Qualitative analyses showed that in the CFP+ group, active involvement in activities of adults with VSPID and number of DSPs' initiatives to stimulate active involvement exceeded those within the two control groups. Discussion: CFP+ has positive effects on the active involvement of individuals with VSPID and on DSPs' initiatives to enhance this involvement. The unexpected small effects of CFP+ on the participation of these adults could be explained by several factors such as small sample size, ceiling effects, response shift, changes in the control group, and implementation barriers. Accordingly, the most effective elements of CFP+ could be further developed and investigated in combination with an improved implementation strategy.